2021
DOI: 10.1177/01436244211013645
|View full text |Cite
|
Sign up to set email alerts
|

Examining the magnitude and perception of summertime overheating in London care homes

Abstract: This paper brings together objective and subjective data on indoor temperature and thermal comfort to examine the magnitude and perception of summertime overheating in two London-based care homes occupying modern and older buildings. Continuous monitoring of indoor and outdoor temperature, relative humidity and CO2 levels was conducted in summer 2019 along with thermal comfort surveys and semi-structured interviews with older residents and staff of the care settings. Indoor temperatures were found to be high (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 28 publications
(40 reference statements)
1
1
0
Order By: Relevance
“…Yet, even in the newer LEED-certified building on site C where smoking was absent and residents reported operating the A/C, less than 50% of indoor HI and PM 2.5 measurements lie within the acceptable zone, which indicates insufficient protection of seniors from overheating and air pollutants. This finding aligns with the results of a monitoring study by Gupta et al, 93 who found severe summertime overheating in a modern 2013-built care home in London, UK, and with the results of Ade and Rehm, 57 who found significant signs of overheating in a green-rated building for retirees in Auckland, NZ during the two warmest months of the year. Substantial variations in indoor thermal and air quality conditions are further revealed by comparing apartments within each site, some of which are counterintuitive.…”
Section: Discussionsupporting
confidence: 90%
“…Yet, even in the newer LEED-certified building on site C where smoking was absent and residents reported operating the A/C, less than 50% of indoor HI and PM 2.5 measurements lie within the acceptable zone, which indicates insufficient protection of seniors from overheating and air pollutants. This finding aligns with the results of a monitoring study by Gupta et al, 93 who found severe summertime overheating in a modern 2013-built care home in London, UK, and with the results of Ade and Rehm, 57 who found significant signs of overheating in a green-rated building for retirees in Auckland, NZ during the two warmest months of the year. Substantial variations in indoor thermal and air quality conditions are further revealed by comparing apartments within each site, some of which are counterintuitive.…”
Section: Discussionsupporting
confidence: 90%
“…Existing studies have pointed out the overheating risk in care facilities during summertime, 58 which also remains in the wintertime. Six factors could influence thermal comfort in a particular scenario: metabolic rate, clothing insulation, air temperature, radiant temperature, airspeed and humidity.…”
Section: Discussionmentioning
confidence: 99%